Pelaksanaan Internal Audit Terhadap Niat Whistleblowing Dalam Rangka Mencapai Good Corporate Governance Melalui Perceived Environmental Uncertainty (Pada Perusahaan Farmasi Di Sidoarjo) - Dina Dwi Oktavia Rini; Wiwit Hariyanto (UMSurabaya Publishing, 2019)
ABSTRACT The aim of this research are (1) to analyze the role of KPU in the implementation of internal audit on private sector organization; (2) to analyze the magnitude of whistleblowing intentions after the implementation of internal audits; (3) to analyze the magnitude of whistleblowing intentions after the implementation of internal audit if influenced by the PEU, (4) to analyze whistleblowing intentions to support the achievement of good corporate governance. This study will use qualitative methods, targeting middle and lower level managers of pharmaceutical companies in Sidoarjo, including: supervisors, department heads, managers. The result of this research is whistleblowing as a manifestation of internal audit which is indirectly influenced by perceived environmental uncertainty can play a role in achieving good corporate governance. The different PEUs play a role in conducting internal audits in increasing whistleblowing intentions between the private sector (pharmaceutical companies)Keywords : Internal Audit, Whistleblowing, and good corporate governanceCorrespondence to : dinador@umsida.ac.id ABSTRAK Tujuan dari penelitian ini adalah (1) untuk menganalisis peran KPU dalam pelaksanaan audit internal pada organisasi sektor swasta; (2) untuk menganalisis besarnya niat whistleblowing setelah pelaksanaan audit internal; (3) untuk menganalisis besarnya niat whistleblowing setelah pelaksanaan audit internal jika dipengaruhi oleh PEU, (4) untuk menganalisis niat whistleblowing untuk mendukung pencapaian tata kelola perusahaan yang baik. Penelitian ini akan menggunakan metode kualitatif, menargetkan manajer level menengah dan bawah dari perusahaan farmasi di Sidoarjo, termasuk: pengawas, kepala departemen, manajer. Hasil dari penelitian ini adalah whistleblowing sebagai manifestasi audit internal yang secara tidak langsung dipengaruhi oleh ketidakpastian lingkungan yang dirasakan dapat berperan dalam mencapai tata kelola perusahaan yang baik. Berbagai PEU berperan dalam melakukan audit internal dalam meningkatkan niat whistleblowing antara sektor swasta (perusahaan farmasi)Kata kunci : Audit internal, Whistleblowing, dan tata kelola perusahaan yang baikKorespondensi : dinador@umsida.ac.id